Screening biorefinery pathways to biodiesel, green-diesel and propylene-glycol: A hierarchical sustainability assessment of process. (15th December 2021) - de Faria, Daniela Ramos G.; de Medeiros, José Luiz; Araújo, Ofélia de Queiroz F.
Abstract: Plant design implies the best choice among a set of feedstock-to-product process pathways. Multiple sustainability performance indicators can blur the decision, and existing sustainability assessment methods usually focus only on environmental life-cycle performance and corporate metrics or solely on the gate-to-gate process. It is relevant to incorporate integrated system analysis to address sustainability comprehensively. To this end, the Sustainable Process Systems Engineering (S-PSE) method was previously introduced to select the most sustainable feedstock-process-product configuration via four-dimensional indicators (environment, efficiency, health-&-safety, and economic), and then pinpoint the sustainability hotspots of the best design to unveil possible improvements. This work expands S-PSE by adding new features: (i) cradle-to-gate environmental assessment; (ii) composition of flowsheets; (iii) new indicators; (iv) statistical screening of indicators; and (v) 2030 Agenda compliance. A biorefinery case-study demonstrates S-PSE: to select the best pathway from soybean-oil, palm-oil, and microalgae-oil to biodiesel, green-diesel, and propylene-glycol. Firstly, statistical screening reduces the indicator set by 62%. Results evince all routes from microalgae-oil as economically unfeasible due to oil cost, despite superior environmental performance. S-PSE evinces palm-oil-to-biodiesel as the most sustainable due to lower cradle-to-gate emissions and manufacturing cost, with sustainability hotspots associated to hazardous methanol input and energy-intensive distillations. 2030 Agenda analysis also outlines palm-oil-to-biodiesel as best for 5 out of 10 Sustainable Development Goals linked to the reduced indicator set. Graphical abstract: Image 1 Highlights: A two-level hierarchical method is proposed to assess sustainability of processes. Assessment includes indicator statistical screening and correlation to 2030 Agenda. Sustainability of 8 biorefinery pathways from 3 bio-oil feedstocks was assessed. Statistical screening reduces the original set of sustainability indicators by 62%. Palm-oil-to-biodiesel was found to be the most sustainable route among 8 pathways.